A highly sensitive ion selective electrochemical sensor amplified with ionic liquid for determination of lanthanum ion in real water samples. Issue 8 (21st June 2022) - Shojaei, Esmat; Masrournia, Mahboubeh; Beyramabadi, Ali; Behmadi, Hossein
ABSTRACT: Lanthanum(La) has been utilised in various industries and entered water samples through the discharge of industrial wastewater. Exposure to La (III) ion can damage some human organisms, such as the nervous system and lungs, and increase the risk of lung cancer. Therefore, the measurement of lanthanum in water samples is very important to control its adverse effects. In this study, a new and cheap potentiometric sensor was developed to determine La(III) ion in real water samples. A carbon paste electrode (CPEs) as an indicator electrode was prepared using graphite powder, commercial ionic liquids as a binder, graphene oxide and a synthetic ligand as an ionophore. The complex reaction between the 2-((2-(5-amino-1, 3, 4-thiadiazol-2-yl)hydrazono)methyl)phenol Schiff base and La(III) ion has been explored by employing the density functional theory (DFT). The results of the theoretical were shown the complex formation La(III) is thermodynamically favourable and confirmed the obtained experimental results. The percentage of components present in La(III) ion electrode was optimised by an experimental design based on D-optimal mixture design, which reduces the cost and time of the electrode optimisation process. A Nernstian behaviour was observed by the electrode in a concentration range from 7.0 × 10 −7 to 1.0 × 10 −1 M to measure La(III) with a correlation coefficient of 0.9832. Also, a low LODs (5.16 × 10 −8 ) and RSDs (2.05%) were obtained with the sensor. Application of the sensor for the real samples was indicated the La(III) sensor can be well utilised for the analyte determination with a suitable recovery (≥97.4).